2018
DOI: 10.1002/jctb.5783
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a SGO/PVDF‐g‐PSSA composite proton‐exchange membrane and its enhanced performance in microbial fuel cells

Abstract: BACKGROUND Proton‐exchange membrane (PEM) has a significant effect on the performance and overall cost of microbial fuel cells (MFCs). In this study, a novel composite PEM is fabricated by compositing sulfonated graphene oxide (SGO) with the Poly(vinylidene fluoride)‐g‐Poly(styrene sulfonic acid) (PVDF‐g‐PSSA) copolymer. The performance of MFCs with these newly prepared composite PEMs as separators was evaluated. A Quartz crystal microbalance with dissipation (QCM‐D) combined with membrane‐coated sensor crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…Using the FTIR spectrum of graphite as a reference, the oxygen functional the asymmetric stretching of SO 3 and the C S stretching vibration because of the presence of the sulfone group. 40,41 The physicochemical properties of graphite powder and its modification were studied by Raman spectroscopy, and the chemical shift of pure graphite powder was observed. In Figure 5B, the peaks at 1597 and 2424 cm À1 are assigned to the G-band and 2D-band, respectively, with an intensity ratio I 2D /I G (area) of 1.8, indicating a bilayer or single-layer graphite, which also has a small lateral size and low crystallinity with high electronic conductivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the FTIR spectrum of graphite as a reference, the oxygen functional the asymmetric stretching of SO 3 and the C S stretching vibration because of the presence of the sulfone group. 40,41 The physicochemical properties of graphite powder and its modification were studied by Raman spectroscopy, and the chemical shift of pure graphite powder was observed. In Figure 5B, the peaks at 1597 and 2424 cm À1 are assigned to the G-band and 2D-band, respectively, with an intensity ratio I 2D /I G (area) of 1.8, indicating a bilayer or single-layer graphite, which also has a small lateral size and low crystallinity with high electronic conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…Upon sulfonation of graphene oxide, a shoulder band appeared overlapping the OH stretch at 2912 cm −1 , which is due to the presence of the sulfonic group. The peaks at 458, 1013, and 1178 cm −1 are attributed to the asymmetric stretching of SO 3 and the CS stretching vibration because of the presence of the sulfone group 40,41 …”
Section: Resultsmentioning
confidence: 99%
“…They found that the PBI had a high CO to hydrogen selectivity in the combustor exhaust. The sensor’s performance using PBI was better than that of Nafion 117 in terms of influence from the humidity. …”
Section: Fundamental Of Fuel-cell-type Gas Sensorsmentioning
confidence: 94%
“…Further, reducing fossil fuel resources provokes the need to find alternative clean and sustainable energy sources. Among various alternative sources, proton exchange membrane fuel cells (PEMFCs) have attracted immense attention owing to their green energy aspect, high efficiency for a prolonged period, stationary power and portability 1,2 . The PEM is considered as a vital part of a PEMFC to provide a proton pathway during oxygen and fuel separation 3 .…”
Section: Introductionmentioning
confidence: 99%